2016
DOI: 10.1620/tjem.238.317
|View full text |Cite
|
Sign up to set email alerts
|

Higher Incidence of Deteriorated Mental Health in Older People Being Mistakenly Labeled as Dementia: A Two-Year Consecutive Community-Dwelling Study in Shanghai, China

Abstract: Dementia has been increasingly paid attention by policymakers in China. However, the majority of the public has an indistinct concept of dementia and its diagnostic criteria. Therefore, many abnormal characteristics and actions of older people are labeled as having dementia while diagnosed without dementia. We examined a multi-stage cluster sample of 11,223 participants aged 60 years and above who have been clinically confirmed by general practitioners as not having dementia in 2013, and 7,861 participants wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Amongst the Chinese population, previous studies found that living alone, poorer socioeconomic status, stroke, having history of depression, excessive drinking and smoking were also associated with poor cognitive performance in developed areas of China (Ding et al 2015;Giri et al 2016;Xie et al 2016;Yang et al 2016). Considering the complex cultural and social backgrounds of China, studies focusing on older Chinese could provide further evidence on this area.…”
Section: Introductionmentioning
confidence: 99%
“…Amongst the Chinese population, previous studies found that living alone, poorer socioeconomic status, stroke, having history of depression, excessive drinking and smoking were also associated with poor cognitive performance in developed areas of China (Ding et al 2015;Giri et al 2016;Xie et al 2016;Yang et al 2016). Considering the complex cultural and social backgrounds of China, studies focusing on older Chinese could provide further evidence on this area.…”
Section: Introductionmentioning
confidence: 99%